Outcomes of cataract surgery in patients previously treated with orbital radiotherapy. Issue 2 (February 2022) - Hind, Jennifer; Jamison, Aaron; Schipani, Stefano; Connolly, Julie; Cauchi, Paul; Chadha, Vikas
Abstract : Cataract surgery in patients previously treated with EBRT has a good safety profile; however, there is a higher risk for CME and PC opacification. Abstract : Purpose: To quantify the risks for cataract surgery in patients who have previously undergone external beam radiotherapy (EBRT). Setting: Tertiary ophthalmology and oncology hospital. Design: Retrospective case series. Methods: Patients treated with orbital EBRT at the Beatson West of Scotland Cancer Centre between 2001 and 2019 were identified, and clinical records were reviewed to identify those who had subsequently undergone cataract surgery. Preoperative and postoperative case records, and operation records, were reviewed to identify demographic data and data regarding complications and surgical outcomes. Results: 46 eyes (of 33 patients) were included. The indications for EBRT included thyroid eye disease, lymphoma, choroidal metastases, and other orbital malignancies. Mean corrected preoperative Snellen visual acuity was 20/100 (range 20/30 to 20/2000) improving to 20/25 (20/12 to 20/160, 1-way analysis of variance P < .01). Mean visual gain was 0.5 logMAR (−0.9 to 1.9). There was 1 case of posterior capsule (PC) rupture with vitreous loss (2%). Dense PC plaque was noted intraoperatively in 19.5% (n = 9). 13% (n = 6) required Nd:YAG laser posterior capsulotomy. There were 6 cases (13%) of cystoid macular edema (CME). Conclusions: Visual outcomes after cataract surgery in this cohort of patients were similar to those obtained in a nationwide cohort. EBRT seemed to be associated with an increased incidence of intraoperative PC plaque, postoperative CME (which in most cases settled with treatment), and need for posterior capsulotomy.